A Legal Phenomenon of Law - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2023)
The scientific article critically examines some features of such a legal phenomenon as a legal norm. Attention is drawn to the fact that some of the features of the rules of law require clarification. In particular, and in particular, such a feature of it as